2021
DOI: 10.1016/j.xphs.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Disintegrant Selection in Hydrophobic Tablet Formulations

Abstract: The hydrophobicity of poorly soluble drugs can delay tablets disintegration. We probed here the influence of different disintegrants on the disintegration of challenging hydrophobic formulations. Tablets containing diluents, hydrogenated vegetable oil and either sodium starch glycolate (SSG), croscarmellose sodium (CCS) or crospovidone (XPVP) were prepared. The disintegration time of tablets was tested immediately and after storage at 40 C and 75% RH in sealed bags. Results show that storage and compression fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was also shown by Sacchetti et al (2017) that the moisture sorption properties of disintegrants cause volume expansion during storage, which in turn results in stress relaxation and prolonged disintegration times, particularly for tablets containing XPVP. This was further confirmed by Bauhuber et al (2021) , who showed that tablets containing XPVP showed the biggest change in disintegration time after storage at 40 ∘ C /75%RH compared to those containing CCS or SSG.…”
Section: Introductionmentioning
confidence: 56%
“…It was also shown by Sacchetti et al (2017) that the moisture sorption properties of disintegrants cause volume expansion during storage, which in turn results in stress relaxation and prolonged disintegration times, particularly for tablets containing XPVP. This was further confirmed by Bauhuber et al (2021) , who showed that tablets containing XPVP showed the biggest change in disintegration time after storage at 40 ∘ C /75%RH compared to those containing CCS or SSG.…”
Section: Introductionmentioning
confidence: 56%